ESTUDOS DE CARACTERIZAÇÃO DE MICROENCAPSULADOS DE RESVERATROL - Souza, Sabrina Ambrósio de Lima; Arruda, Rodolfo Êlleson dos Santos; Nascimento, Ticiano Gomes do (Gep News, 2017)
Tipo de Apresentação: Comunicação oral